IoTTECH : TECHNOLOGY INTERNET OF THINGS (IoT) UNTUK PENGATURAN OTOMATIS KELEMBABAN & TEMPERATUR RUANGAN BUDIDAYA JAMUR TIRAM (PLEUROTUS OSTREATUS) - Marcell Petrus Saptono; Yusverison Andika (Electro Luceat, 2020)
The results of the IoTTech Internet of Things (IoT) tool for Oyster Mushroom cultivation control the temperature and humidity of the Oyster Mushroom cultivation house. This IOTTECH technology has a DHT11 sensor input to be processed to the Arduino mega and ethernet shield while the output of this tool is an android smartphone, actuator, humidity and temperature control using the Blynk application. The initial process with the DHT11 sensor sends data to the microcontroller for the process of displaying the output value of humidity, LDR and temperature, the output is displayed on an android smartphone as a monitoring interface with the Blynk application as remote monitoring. This research produced a prototype for the output humidity, LDR and air temperature in mushroom houses using the Internet of Thing (IoT) using Blynk. The regulation of output humidity, LDR and temperature uses IoT via blynk, more efficient both in terms of time and cost. The actuator will live automatically according to the humidity, LDR and temperature that has been set.